Experimental validation of a FLUKA Monte Carlo simulation for carbon-ion radiotherapy monitoring via secondary ion tracking - Ochoa-Parra, Pamela; Schweins, Luisa; Abbani, Nelly; Ghesquière-Diérickx, Laura; Gehrke, Tim; Jakubek, Jan; Marek, Lukas; Granja, Carlos; Dinkel, Fabian; Echner, Gernot; Winter, Marcus; Mairani, Andrea; et al. (Medical physics, 2024)
Background In-vivo monitoring methods of carbon ion radiotherapy (CIRT) includes explorations of nuclear reaction products generated by carbon-ion beams interacting with patient tissues. Our research group focuses on in-vivo monitoring of CIRT using silicon pixel detectors. Currently, we are conducting a prospective clinical trial as part of the In-Vivo Monitoring project (InViMo) at the Heidelberg Ion Beam Therapy Center (HIT) in Germany. We are using an innovative, in-house developed, non-contact fragment tracking system with seven mini-trackers based on the Timepix3 technology developed at CERN. Purpose This article focuses on the implementation of the mini-tracker in Monte Carlo (MC) based on FLUKA simulations to monitor secondary charged nuclear fragments in CIRT. The main objective is to systematically evaluate the simulation accuracy for the InViMo project. Methods The implementation involved integrating the mini-tracker geometry and the scoring mechanism into the FLUKA MC simulation, utilizing the finely tuned HIT beam line. The systematic investigation included varying mini-tracker angles (from \15^°\ to \45^°\ in \5^°\ steps) during the irradiation of a head-sized phantom with therapeutic carbon-ion pencil beams. To evaluate our implemented FLUKA framework, a comparison was made between the experimental data and data obtained from MC simulations. To ensure the fidelity of our comparison, experiments were performed at the HIT using the parameters and setup established in the simulations. Results Our research demonstrates high accuracy in reproducing characteristic behaviors and dependencies of the monitoring method in terms of fragment distributions in the mini-tracker, track angles, emission profiles, and fragment numbers. Discrepancies in the number of detected fragments between the experimental data and the data obtained from MC simulations are less than 4% for the angles of interest in the InViMo detection system. Conclusions Our study confirms the potential of our simulation framework to investigate the performance of monitoring inter-fractional anatomical changes in patients undergoing CIRT using secondary nuclear charged fragments escaping from the irradiated patient.